THE EFFECT OF CAPITAL STRUCTURE, COMPANY GROWTH, AND INFLATION ON FIRM VALUE WITH PROFITABILITY AS INTERVENING VARIABLE (STUDY ON MANUFACTURING COMPANIES LISTED ON BEI PERIOD 2014 - 2018) - Topani Suzulia, Maya; Sudjono; Ahmad Badawi Saluy (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The purpose of this research is to test and analyze the effect of capital structure, company growth, and inflation on firm value with profitability as intervening variable. The population in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2014 - 2018 totaling 174 companies. Determination of the sample is selected by purposive sampling. Out of 174 populations, only 27 samples were selected. The type of research data is panel data. Path analysis was chosen as the method of data analysis. The results shows that partially capital structure has a significant effect on firm value, company growth and inflation have no significant effect on firm value, capital structure has a significant effect on profitability, company growth and inflation have no significant effect on profitability, profitability has a significant effect on firm value. Profitability mediates the effect of capital structure on firm value, profitability does not mediate the effect of company growth and inflation on firm value.